IMPLEMENTASI TANGGUNGJAWAB NEGARA BERKAITAN DENGAN HAK ATAS PENDIDIKAN DASAR BAGI WARGA NEGARA DI DESA TERPENCIL KABUPATEN BANGLI - Sri Utari, Ni Ketut; Udiana, I Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 4 (2015), 2015)
The purpose of this study is to analyze the implementation of Article 31 (2) of the Constitution 1945 concerning the right of education for citizens, especially in remote village of Bangli Regency, Bali Province. The type of this research is empirical legal research. The study showed that the Government has provided a central school in one building both for elementary and junior high school so called “Satap” (School in one roof) in order to fulfill its constitutional obligation for the people in slop of mountains in the remote village of Bangli Regency. For this efforts are  supported by education funding of the National Government distributes budget operational school (BOS), grants of educational facilities from Government Budget of Bali Province (APBD Bali) as well as  Block Grand from the National Government Budget (APBN). However, those budgets are still considered relatively very small. For the better implementation of the right of education, therefore the efforts of government need to be improved as well as budgeting for the remote village should be prioritized, increased and supervised
Keywords: state responsibility; basic education; remote village